Prevalence, Risk Factors and Management Strategies for Cardiovascular Diseases in Kashmir, India: A Comprehensive Study - Faisal Qadri, Syed Mohd.; Khan, Mohd. Faisal; John, Sakhi; Farooqui, Noria (Journal of Neonatal Surgery, 2025)
This study investigates the prevalence, risk factors and management challenges of cardiovascular diseases (CVDs) in Kashmir, India, aiming to identify effective strategies to improve cardiac event outcomes. Using primary data from 20 healthcare professionals, the findings reveal a high perceived CVD burden, with 40% rating cardiac care as "Good" and 30% as "Fair." Key barriers include inadequate infrastructure (75%), low patient awareness (70%), and financial constraints (60%), with diagnostic services widely available (90%) but cardiac surgery (50%) and rehabilitation (40%) limited. Regression analyses confirm infrastructure (β=0.42, p=0.005) and awareness (β=0.38, p=0.008) as major drivers of prevalence, while awareness (β=0.45, p=0.004) and financial constraints (β=0.35, p=0.012) exacerbate risk factor severity. A Chi-Square test (p=0.024) indicates experienced professionals are more critical of policy effectiveness. Recommended strategies enhanced training (70%), infrastructure upgrades (75%), and community education (60%) aim to address these gaps. The study underscores the need for systemic reforms, including policy revisions and resource diversification, to reduce CVD burden and enhance cardiac care in Kashmir